Gaya Bahasa Kiasan dalam Antologi Puisi Malam Tamansari Karya Suminto A. Sayuti dan Alternatifnya sebagai Bahan Ajar Puisi Kelas X - Kusuma, Akbar Wika Putra; Pramono, Dedi (Kajian Bahasa dan Sastra (KABASTRA), 2025)
This study analyzes the importance of understanding figurative language in poetic works, particularly in the poetry anthology "Malam Tamansari" by Suminto A. Sayuti, which is rich in aesthetic and local cultural values. This study aims to describe the types of figurative language found in the anthology and examine their relevance as alternative poetry teaching materials for 10th graders in high school. This study utilizes Gorys Keraf's theory of figurative language, which classifies figurative language into rhetorical and figurative language styles such as simile, metaphor, allegory, personification, and others. The research method used is descriptive qualitative and employs a stylistic approach. Data were collected through careful and systematic note-taking of the contents of the "Malam Tamansari" poetry collection, then analyzed and classified based on the types of figurative language identified. Data validity was checked using researcher triangulation to ensure the accuracy and objectivity of the analysis. The results of this study indicate that there are twelve types of figurative language styles found in the Malam Tamansari poetry anthology, namely simile, metaphor, allegory, personification, allusion, eponym, epithet, synecdoche, metonymy, hypalase, irony, and innuendo. The dominant figurative language style found in this work is metaphor. In addition, this poetry anthology has met the criteria of linguistic, psychological, and cultural background aspects so that it is suitable to be used as an alternative poetry teaching material for grade X high school students. Knowledge of figurative language styles is expected to improve students' understanding, appreciation, and creative abilities in literature learning.